An ontology-based approach supporting holistic structural design with the consideration of safety, environmental impact and cost. (January 2018) - Zhang, Jisong; Li, Haijiang; Zhao, Yinghua; Ren, Guoqian
Highlights: A holistic approach to support multi-objective structural design across different sectors is developed. Environmental impact and safety along with cost are holistically considered through reasoning based knowledge processing. NSC and HPC together with UHPC are used as structural material for comparison of alternatives. Abstract: Early stage decision-making for structural design critically influences the overall cost and environmental performance of buildings and infrastructure. However, the current approach often fails to consider the multi-perspectives of structural design, such as safety, environmental issues and cost in a comprehensive way. This paper presents a holistic approach based on knowledge processing (ontology) to facilitate a smarter decision-making process for early design stage by informing designers of the environmental impact and cost along with safety considerations. The approach can give a reasoning based quantitative understanding of how the design alternatives using different concrete materials can affect the ultimate overall performance. Embodied CO2 and cost are both considered along with safety criteria as indicative multi-perspectives to demonstrate the novelty of the approach. A case study of a concrete structural frame is used to explain how the proposed method can be used by structural designers when taking multi performance criteria into account. The major contribution of the paper lies on the creation of a holistic knowledge base which links through different knowledge across sectors to enable the structural engineer to come up with much more comprehensive decisions instead of individual single objective targeted delivery.